Gender equality and social inclusion in NDC planning and implementation in Africa - Huyer, Sophia (2024)
The analysis assessed the integration of key groups identified in the Paris Agreement into NDC planning and implementation in African countries, in the same sectors of agriculture, livestock and CSA: women, youth, indigenous peoples (IPs), elderly and people with disabilities. The analysis focused on identification of actions, strategies and action plans that indicate concrete planning and action toward implementation of NDC commitments in those three sectors. National documents analyzed for this assessment included strategies, action plans, tools, instruments, data collection or analysis protocols, and monitoring.